Pakistan : Staff Report for the First Review Under the Extended Arrangement Under the Extended Fund Facility, Request for Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper provides an update on economic and policy developments in Pakistan since the issuance of the IMF staff report on December 11, 2013. Gross official reserves were USD 3.4 billion as of December 16, 2013, in line with IMF staff projections. The State Bank of Pakistan purchased an additional USD 75 million on top of the USD 200 reported in the staff report in the foreign exchange spot market as part of the continued effort to build reserves. The exchange rate rebounded slightly and was down some 8 percent against the dollar since the end of June. Headline inflation reached 10.9 percent year over year in November from 9.1 percent in October. This is in line with IMF staff projections and mainly reflects food price increases.